Body Mass Index, Central Obesity Relationship Between Blood Lipid Levels and Snoring - YAZAR, H.; TIFTIK, A.M.; BYKBA, SADAK (Asian Journal of Chemistry, 2010)
Obesity is an excessive fat deposits, is still worldwide increase. Many metabolic disorders of obesity are believed to be caused by abdominal central fat (central or abdominal obesity). In present studies, a relationship between blood lipid levels and BMI, obsity and snoring is established.